2013
DOI: 10.1002/rcm.6748
|View full text |Cite
|
Sign up to set email alerts
|

On‐line HfF5/WF5 separation in an O2‐filled radiofrequency quadrupole gas cell

Abstract: This result advances the possibility of detecting natural (182)Hf when AMS is supplemented with an isobar separator in the injection system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Di↵erences in electronic structure of anions can also be exploited in anion-gas reactions at eV energies and O 2 was found particularly well suited for HfF 5 -WF 5 separation, providing an isobar suppression of at least 10 3 in an earlier study [25]. While the exact reaction channel remained elusive, Zhao et al [25] argued that HfF 5 , being a superhalogen anion, is extraordinarily stable and, thus, highly immune to electron charge transfer reactions, collisional detachment and association or transformation of molecules at eV energies.…”
Section: Gas Reaction Studiesmentioning
confidence: 85%
“…Di↵erences in electronic structure of anions can also be exploited in anion-gas reactions at eV energies and O 2 was found particularly well suited for HfF 5 -WF 5 separation, providing an isobar suppression of at least 10 3 in an earlier study [25]. While the exact reaction channel remained elusive, Zhao et al [25] argued that HfF 5 , being a superhalogen anion, is extraordinarily stable and, thus, highly immune to electron charge transfer reactions, collisional detachment and association or transformation of molecules at eV energies.…”
Section: Gas Reaction Studiesmentioning
confidence: 85%
“…−95 kcal mol −1 . The formation of the dimer coordinated to seven F − ions shows the high affinity of Hf(IV) to fluoride, as demonstrated by the dimeric crystalline structure [Hf 2 F 8 (H 2 O) 6 ], [30] and the resistance of the superhalogen anion [HfF 5 ] − to reactions with O 2 [31] …”
Section: Resultsmentioning
confidence: 99%
“…[29] The formation of the dimeric species (H 3 O) 3 [30] and the resistance of the superhalogen anion [HfF 5 ] À to reactions with O 2 . [31] The (H 3 O) 2 [21] and HfF 4 • 3H 2 O. [30] The anionic species of Hf(IV) did not show the same sequence of thermodynamic stability (Table 3) compared to the species of Zr(IV).…”
Section: Thermodynamic Analysis Of Hf(iv)mentioning
confidence: 94%
“…In an additional application, Hf and W fluoroanions were generated from the PbF 2 matrix. Since HfF 5 − and WF 5 − were both formed, there was still a problem with overlap of isobaric isotopic ions, which cause interference problems for the measurement of extreme isotope ratios by AMS . However, it was found that the tungsten species could be attenuated by reaction with O 2 or NO 2 , enabling measurement of the trace isotopes of Hf.…”
mentioning
confidence: 99%